Implementasi Program BPJS Ketenagakerjaan bagi Nelayan di Kelurahan Pasia Nan Tigo Kecamatan Koto Tangah Kota Padang - Putri Wahyuni; Intan Slipilia (Al-DYAS, 2026)
The BPJS Ketenagakerjaan social security program is an important protection instrument for workers in both the formal and informal sectors, including fishers who face high occupational risks and unstable incomes, yet its implementation still encounters various obstacles that hinder the sustainability of membership. This study aims to analyze the implementation of the BPJS Ketenagakerjaan program for fishers in Pasia Nan Tigo Urban Village, Koto Tangah Subdistrict, Padang City, and to identify the constraints encountered in its implementation. A qualitative method with a descriptive approach was employed to examine how the program is executed and the extent to which employment social security protection is actually received by fishers. The findings show that although the BPJS Ketenagakerjaan program has been implemented and provides initial protection for fishers, its implementation has not been optimal due to constraints related to communication, resources, disposition, and bureaucratic structure. This is reflected in the low coverage of membership, whereby out of 1,450 fishers only 119 individuals (8.21%) were registered in 2024 and all were classified as inactive because they did not continue paying contributions independently after the subsidy period ended, resulting in non-sustainable social security protection for fishers. The main constraints identified include the continuity of self-funded contribution payments, fishers’ low understanding of the program, socialization limited to the initial phase, and restricted budget allocations for contribution subsidies. These findings confirm that the program’s objectives to provide social security protection and foster the independence of fishers have not been achieved optimally, indicating the need to strengthen policy communication strategies, enhance institutional capacity, expand and sustain contribution subsidy schemes, and intensify education efforts to ensure the continuity of fishers’ participation in the BPJS Ketenagakerjaan program.